Mapping the occupational segregation of white women in the US: Differences across metropolitan areas - Olga Alonso-Villar; Coral Del Río (European Regional Science Association (ERSA), 2015)
This paper seeks to investigate the occupational segregation of white women in the U.S. at the local labor market level, exploring whether the segregation of this group is a homogeneous phenomenon across the country or there are important disparities in the opportunities that these women meet with across American urban areas. As opposed to other studies that are based on pair-wise comparisons between groups (e.g., white women versus white men, white women versus black women, and so on) and calculate an index?mainly the index of dissimilarity?for each of these comparisons, this paper use segregation measures that permit one to offer a single value for white women (Alonso-Villar and Del Río, 2010). The results based on 273 metropolitan areas show substantial variation across areas. The proportion of white women working in a metropolitan area who would have to shift occupations to achieve zero segregation without changing the occupational structure of the area ranges between 20% and roughly 40%. An important contribution of this paper is that, apart from quantifying the extent of segregation, it also assesses the consequences of that segregation taking into account the ?quality? of occupations that the group tends to fill or not to fill. The analysis reveals that although segregation brings white women as a whole a per capita estimated gain of 1% of the average wage of the country, in some MAs these women have gains of around 21% of the average wage in the area while in others they instead have losses of 11%. Therefore, an analysis of segregation of white women at the national level seems to mask the real situation of this group. Apart from the disadvantages that white women face in terms of receiving lower wages than their male counterparts working in the same occupation and MA, the occupational distribution of these women remains an issue to deal with in many local labor markets. This paper goes one step further by attempting to explain the disparities that exist across areas. By undertaken both counterfactual and regression analyses, it investigates whether the spatial disparities that exist in the gains/losses of white women associated to their segregation arise from territorial differences in a) the educational level of white women, b) the gender-race composition of the labor force, c) the relative pay of occupations, d) the industrial structure, and e) the state in which the area is located. The analysis shows that differences among states are significant even after controlling for demographic, educational, industrial, and earning variables.
Keywords: R23; J15; J16; J71; D63; 330; Occupational segregation; well-being; metropolitan areas; gender; race